Achieving high-quality universal health coverage: a perspective from the National Health Service in England. Issue 6 (4th December 2018) - Friebel, Rocco; Molloy, Aoife; Leatherman, Sheila; Dixon, Jennifer; Bauhoff, Sebastian; Chalkidou, Kalipso
Abstract : Governments across low-income and middle-income countries have pledged to achieve universal health coverage by 2030, which comes at a time where healthcare systems are subjected to multiple and persistent pressures, such as poor access to care services and insufficient medical supplies. While the political willingness to provide universal health coverage is a step into the right direction, the benefits of it will depend on the quality of healthcare services provided. In this analysis paper, we ask whether there are any lessons that could be learnt from the English National Health Service, a healthcare system that has been providing comprehensive and high-quality universal health coverage for over 70 years. The key areas identified relate to the development of a coherent strategy to improve quality, to boost public health as a measure to reduce disease burden, to adopt evidence-based priority setting methods that ensure efficient spending of financial resources, to introduce an independent way of inspecting and regulating providers, and to allow for task-shifting, specifically in regions where staff retention is low.